(untitled) (Historia, 2021)
In the wake of contemporary African states’ renewed investments in large-scale infrastructure and other spectacular projects, there is once again a growing interest in understanding the history of modernisation and modernity in Africa. This edited collection bridges the crucial years of late colonialism into roughly the first decade of independence to examine what it refers to as “modernization as spectacle” – the ways that modernisation and notions of modernity met in publically enacted institutions, policies, and projects. Approaching modernisation as a transnational, contested and ideologically driven project, the book tracks how seemingly disparate spheres and undertakings were linked by the ideas that underpinned the actual material and institutional instantiations of modernisation spectacles. Thereby, it provides a compelling understanding of the interplay between modernity and modernisation.